Brackish water irrigation boosts honeysuckle (Lonicera japonica Thunb.)-salt tolerance by regulating sodium partitioning and potassium homeostasis: implications for coastal saline soil - Shi, Yu; Wang, Xiaojie; Zhang, Kaipeng; Liu, Xuepeng; Xia, Jiangbao; Zhang, Dongjie; Zhang, Xiaoshuai; Cao, Qiqi; He, Wenjun (Frontiers in Plant Science, 2025)
IntroductionAgricultural development in coastal saline-alkali lands is constrained by freshwater scarcity. Utilizing brackish water for irrigation presents a viable pathway to alleviate this pressure. Honeysuckle (Lonicera japonica Thunb.), a salt-tolerant medicinal plant, holds promise for the ecological restoration of these areas. However, the regulatory mechanisms by which brackish water irrigation affects ionic homeostasis and physiological traits in honeysuckle remain elusive.MethodsA field experiment was conducted in the coastal saline-alkali soils of the Yellow River Delta. A randomized complete block design was employed with four brackish water irrigation regimes: T1 (rainfed control), T2 (40 mm), T3 (80 mm), and T4 (120 mm). The effects of these irrigation treatments on ion dynamics within the soil-plant system and the salt tolerance of honeysuckle were analyzed.ResultsWith increasing brackish water irrigation, (1) significantly reduced cation accumulation in the topsoil. Compared to T1, the soil Na+ content under T2, T3, and T4 decreased by 33.69%, 33.94%, and 56.53% in 2019, and by 29.53%, 41.46%, and 59.31% in 2020, respectively. Similarly, the soil K+ content decreased by 3.20%, 27.48%, and 38.78% in 2019, and by 33.58%, 46.77%, and 52.80% in 2020 under the same treatments. (2) In honeysuckle, selective sodium partitioning and potassium homeostasis enhanced the leaf K+/Na+ ratio. The ratio in T4 was 165.45%, 89.90%, and 48.89% higher than in T1, T2, and T3, respectively—a response driven by a 59.27% reduction in leaf Na+ and a 7.24% increase in leaf K+ in T4. (3) alleviated salt-induced oxidative stress in the leaves, reducing the malondialdehyde (MDA) content from 228.46 nmol•g-1 (T1) to 143.81 nmol•g-1 (T4) and decreasing hydrogen peroxide (H2O2) by 43.42%. Concurrently, the whole-plant biomass under T4 (829.56 g) exhibited an 8.8-fold increase versus T1 (94.05 g), while the total Na+ accumulation per plant increased from 351.66 mg (T1) to 1391.97 mg (T4).DiscussionThe findings demonstrate that brackish water irrigation mitigates Na+ accumulation in the root zone through leaching. Honeysuckle maintains ionic homeostasis by restricting Na+ uptake at the root level, facilitating selective Na+ translocation in stems, and regulating the K+/Na+ ratio in leaves. This coordinated physiological strategy ultimately enhances biomass.